Interdisciplinary Approaches to Arabic Language Learning: Enhancing Engagement and Global Competence: Language Learning - Yusuf, Tajudeen (Al-Ḍād Journal, 2024)
This paper investigates the potential of interdisciplinary programs to enhance Arabic language learning by integrating it with disciplines such as business, international relations, and cultural studies. The study is grounded in empirical research conducted across several educational institutions where interdisciplinary approaches have been implemented. By analyzing quantitative data from student performance metrics, enrollment figures, and retention rates, alongside qualitative data from student and faculty interviews, the paper provides a comprehensive evaluation of these programs. The findings indicate that students enrolled in interdisciplinary Arabic programs exhibit higher engagement and improved language proficiency compared to those in traditional language courses. Furthermore, these programs have been shown to attract a more diverse student body, including those who may not have otherwise pursued Arabic studies. However, the research also identifies significant challenges, such as the complexity of curriculum design and the need for specialized faculty training. The paper concludes with recommendations for best practices in developing and sustaining successful interdisciplinary Arabic language programs, emphasizing the importance of strategic resource allocation, robust faculty collaboration, and targeted recruitment efforts. These insights contribute to the broader discourse on language education, offering a model for enhancing the relevance and accessibility of Arabic language learning in a globalized context. Keywords: Interdisciplinary Programs, Arabic Language Education, Student Engagement, Global Competence, Curriculum Design, Multidisciplinary Education